Water Resource Management in Mehsana: Strategies, Challenges, and Sustainable Approaches - Kuntal V. Chaudhari,; Dr. Akhilesh Kumar, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The concern of water resource management is relevant to the Mehsana district of Gujarat because of factors such as semi-arid climate, increased industrialization, and rising agriculture requirements. The focus of this paper is the details of current practices for water management, issues that affect its provision, and the use of sustainable practices for water management in the future. Overusing the resource for purposes such as irrigation also reduces the groundwater table's discharge rate, thus reducing water availability in the area. Moreover, threats from industrial effluent and water pollution by high fluoride levels affect the communities' health. To overcome these problems, integrated water management measures like rainwater harvesting, efficient micro irrigation, and aquifer recharge structures have been developed. The water availability has been improved by government schemes like Saurashtra Narmada Avtaran Irrigation (SAUNI) Yojana and check dam construction. Despite this, some problems are related to the effective implementation of the regulations, mobilization of the community, and water usage issues by agriculture and industry.